Derivatives and Volatility on Indian Stock Markets: The Impact of Derivative Introduction on Volatility and Trading Volume in Indian Stock Markets (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper  summarizes the  theoretical  and empirical  research  on how  the introduction  of derivative  securities  affects the  underlying  market. A  wide  array of theoretical approaches has been applied to the question of howspeculative trading, the introduction of futures, or the introduction ofoptions might affect the stability, liquidity and price informativeness ofasset markets. In most cases, the resulting models predict that speculativetrading and derivative markets stabilize the underlying  market under certain  restrictive conditions,  but  in general  the  predictions can  go  either way, depending on parameter values. The empirical evidence suggests thatthe introduction of derivatives  does notdestabilize the underlying market—either there is no effect or there is adecline in volatility—and that the introduction of derivatives tends to improvethe liquidity and informativeness of markets. In this paper we analyze the effect of the introduction of derivatives(futures and options)  in  the Indian  market  on the  volatility  and on  the  trading volume  of  the underlying index. The period analyzedcovers from April 2001 to March 2006. To study this effect, we use three modelsof  conditional  volatility GARCH, EGARCH and GJR. We  find significant  impact  on variance:  the  evidence indicates  that  the conditional volatility of the underlying index declines after derivativemarkets are introduced. The trading volume  of  NSE (National  Stock  Exchange of  India)  Nifty  -50   increases significantly. Inaddition, the introduction of the derivative contracts in India confirms adecrease in uncertainty in the underlying market and an increase in liquidity,which possibly enhance their efficiency..